Antibacterial And Synergistic Potential of Hibiscus sabdariffa and Zingiber officinale Against Multidrug-Resistant Bacteria - Abdulazeez Mumsiri Abaka; Bristone Pola James; Mohammed Dangana Badamasi; Adamu Aliyu Usman (Biology, Medicine, & Natural Product Chemistry, 2025)
Antimicrobial resistance (AMR) is a global health challenge, particularly in developing regions where access to effective drugs is constrained. Medicinal plants provide an alternative due to their affordability, availability, and wealth of bioactive compounds. This study investigated the antibacterial properties of Zingiber officinale (ginger) and Hibiscus sabdariffa (roselle), both widely used in African traditional medicine, against selected bacterial pathogens. Methanolic extracts were prepared from dried rhizomes of ginger and calyces of roselle, and concentrations of 100%, 95%, 90%, and 85% were tested. Antibacterial activity was determined against Staphylococcus aureus, Escherichia coli, and Pseudomonas sp. using agar well diffusion. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were established by serial dilution and subculture techniques. Statistical significance was assessed using one-way ANOVA and Duncan’s multiple range test at p < 0.05. Phytochemical analysis revealed steroids, terpenoids, and flavonoids in both plants. Ginger additionally contained saponins, alkaloids, tannins, and carbohydrates, whereas roselle uniquely presented cardiac glycosides. Antibacterial activity increased with concentration, with the 100% extracts showing the highest inhibition zones. The combined extract consistently produced larger inhibition zones compared to the individual extracts (p < 0.05). Ginger exhibited the strongest individual activity against S. aureus, while the combined extract was most effective against E. coli. Pseudomonas sp. was the least susceptible. MIC values confirmed these observations: S. aureus was the most sensitive (25 mg/mL), while E. coli and Pseudomonas sp. each recorded 50 mg/mL. MBC values were uniformly 50 mg/mL across all test organisms. The results demonstrate that ginger and roselle possess significant antibacterial properties, with ginger showing superior individual efficacy and roselle providing complementary metabolites that enhanced combination effects. Their synergistic action supports traditional polyherbal therapy and indicates potential as cost-effective, plant-based interventions against AMR. The findings underscore the need for further research to develop standardized formulations for therapeutic application.